1992
DOI: 10.1159/000284763
|View full text |Cite
|
Sign up to set email alerts
|

The Symptom Check List SCL-90-Rand Its Ability to Discriminate between Dysthymia, Anxiety Disorders, and Anorexia nervosa

Abstract: The factorial and discriminative validity of the Hopkins Symptom Check List SCL-90-R were examined in the light of criticism that clinical self-rating scales primarily express a general distress factor. In a population of 899 psychosomatic patients, high intercorrelations were found between the individual dimensions of the SCL-90-R. A subsequent Principal Components Analysis obtained 9 factors which were markedly less interdependent than those in the original version. The ability of the questionnaire to distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…The internal consistency (Cronbach's alpha) in our sample varied between 0.79 and 0.88 for the different subscales. Several studies have reported high intercorrelation among subscales (Carpenter & Hittner, 1995;Holi et al, 1998;Rief & Fichter, 1992;Vassend & Skrondal, 1999), which was confirmed in our study, with the mean Pearson's correlation between scales being 0.67 in the patient group (r ¼ 0.42-0.80) and 0.71 in the control group (r ¼ 0.52-0.84). All correlations between subscales were significant at p < 0.001.…”
Section: Instrumentssupporting
confidence: 89%
“…The internal consistency (Cronbach's alpha) in our sample varied between 0.79 and 0.88 for the different subscales. Several studies have reported high intercorrelation among subscales (Carpenter & Hittner, 1995;Holi et al, 1998;Rief & Fichter, 1992;Vassend & Skrondal, 1999), which was confirmed in our study, with the mean Pearson's correlation between scales being 0.67 in the patient group (r ¼ 0.42-0.80) and 0.71 in the control group (r ¼ 0.52-0.84). All correlations between subscales were significant at p < 0.001.…”
Section: Instrumentssupporting
confidence: 89%
“…Subgroups of depression have as yet not been investigated using the SCL-90R. Although Rief and Fichter [56] were able to confirm differences in profile shapes of the SCL-90R among different diagnostic groups (dysthymia, anxiety disorder, anorexia nervosa), a factor Vetter/von Pritzbuer/Jungmann/Kropp/ Köller analysis in nonselected young men (nonclinical sample) had difficulty in reproducing the factors anxiety [56,57] and psychoticism [57]. It has therefore been proposed that the factors anxiety and psychoticism should be redefined [56].…”
Section: Discussionmentioning
confidence: 99%
“…The 90 items of the SCL-90-R are related to nine subscales: somatization, obsessive compulsive, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation and psychoticism and can be summarized to a global parameter, the global severity index (GSI). As it is recommended to interpret one 'distress factor' rather than the subscale scores of the symptom checklist, mainly because of the high intercorrelations of the nine factors [15,16] , only the GSI was included in statistical analysis. Nevertheless, all subscale scores are reported for comparability of data.…”
Section: Methodsmentioning
confidence: 99%